1993
DOI: 10.1038/365340a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of human IgE synthesis in B cells by mast cells and basophils

Abstract: Immunoglobulin E (IgE) is central to the induction of allergic diseases through its binding to the high-affinity receptor (Fc epsilon R1) on mast cells and basophils. Crosslinking by allergens of the bound IgE leads to the release of various inflammatory mediators. IgE production by B cells requires a physical interaction with T cells, involving a number of surface adhesion molecules, as well as the soluble factors interleukin-4 (IL-4) and IL-13 (ref. 5) produced by T cells, basophils and mast cells. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
323
2
7

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(343 citation statements)
references
References 29 publications
11
323
2
7
Order By: Relevance
“…We therefore also examined the expression of TNF-TNFR family molecules on BMCMCs. It has been reported that human mast cell lines and tissue mast cells can express CD40L (CD154), and mast cell-derived CD40L is thought to contribute to IgE production by B cells (38,39). However, we did not detect any CD40L expression on BMCMCs in our experiments (Fig.…”
Section: Expression Of Members Of the Tnf And Tnfr Families Of Molecucontrasting
confidence: 62%
“…We therefore also examined the expression of TNF-TNFR family molecules on BMCMCs. It has been reported that human mast cell lines and tissue mast cells can express CD40L (CD154), and mast cell-derived CD40L is thought to contribute to IgE production by B cells (38,39). However, we did not detect any CD40L expression on BMCMCs in our experiments (Fig.…”
Section: Expression Of Members Of the Tnf And Tnfr Families Of Molecucontrasting
confidence: 62%
“…Similar observations of isotype switching have been made by SAXON et al [22] in nasal mucosal cells. Not only T-cells but also mast cells and basophils have the capacity to stimulate IgE synthesis by B-cells, as producers of IL-4 and IL-13 and by the interaction of mast cells CD154 (CD40 ligand) with B-cell CD40 [18,30,31]. The mast cell/basophilic induction and stimulation of B-cell IgE-production indicate that immunoglobulin switching, previously thought to take place only in lymph node germinal centres, may also occur in peripheral organs such as the nose.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding ligand CD40L is transiently expressed on activated T cells [28][29][30][31], natural killer (NK) cells [32], mast cells, basophils [33] and eosinophils [34]. CD40 and CD40L are members of the tumour necrosis factor (TNF) receptor ligand family [35,36] and key players in T cell-B cell and T cell-antigen-presenting cell (APC) interaction [37,38].…”
Section: Introductionmentioning
confidence: 99%